Pengaruh Pengawasan Dan Motivasi Terhadap Disiplin Kerja Pegawai Pada Dinas Pariwisata Dan Kebudayaan Kabupaten Karo - Menanti Sembiring; Ingan Ukur Sitepu (Universitas Quality, 2019)
This research is aim to find out how the influence of supervision and working motivation towards discipline of work to employee of Tourism and Culture Department, Karo District. The number of population on this research is about 37 people and all of those made as sample or total sample. For verifying hypothesis which is proposed, there will be done with partial examination, simultaneous examination, and coefficient of determination. The result shows that in partially, variable of supervission and motivation influences discipline of work to employee of Tourism and Culture Department significantly, where the value of tcalculated in supervission variable is 2.272 and value that is calculated according to variable of motivation is 4.431, whereever value of ttableis 1.687. While with simultaneous examination, Fcalculated is calculated with 32, 112 and the value of Ftable is 3.267. So, it is concluded that with simultaneous examination, variable of supervission and motivation influences discipline of work to employee of Tourism and Culture Department significantly too. The result of multiple linear regression obtained with this equation, y = 9,516 + 0,2321X1 + 0,497X2 + e. The Coefficient of determination stated that 0,654 or 65,4 % of discipline of work to employee of Tourism and Culture Department is influenced by supervission and motivation and the residual 34,6 % is influenced by another factor which isn’t researched on this study.